2001
DOI: 10.1152/ajplung.2001.281.1.l183
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hypoxia-induced spontaneous and rhythmic contractions in the rat main pulmonary artery

Abstract: The effect of chronic hypoxia (CH; 1-4 wk) on the electromechanical properties of the rat main pulmonary artery (MPA) was investigated. MPA rings obtained from rats exposed for 14 days to hypobaric (50.5 kPa) CH exhibited spontaneous and rhythmic contractions (SRCs) that were never observed in control (normoxic) rats. SRCs were unaffected by tetrodotoxin, phentolamine, BQ-123 and BQ-788, N-nitro-L-arginine methyl ester, or endothelium removal. CH depolarized smooth muscle cells from -58.8 +/- 9 to -38.6 +/- 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
33
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 29 publications
10
33
1
Order By: Relevance
“…The vasoconstriction was not due to the inhibition of EDHF activity, because neither agent inhibited the EDHF-mediated vasodilation, and charybdotoxin plus apamin did not elicit the response. In contrast to its vasoconstrictor effect in perfused hypertensive lungs, 18␣-glycyrrhetinic acid inhibits spontaneous contractions and causes relaxation of hypertensive main pulmonary arteries from chronically hypoxic rats (4).…”
Section: Discussionmentioning
confidence: 94%
“…The vasoconstriction was not due to the inhibition of EDHF activity, because neither agent inhibited the EDHF-mediated vasodilation, and charybdotoxin plus apamin did not elicit the response. In contrast to its vasoconstrictor effect in perfused hypertensive lungs, 18␣-glycyrrhetinic acid inhibits spontaneous contractions and causes relaxation of hypertensive main pulmonary arteries from chronically hypoxic rats (4).…”
Section: Discussionmentioning
confidence: 94%
“…The rhythmic contraction of pulmonary artery was reported in different types of PAH models in rats, which is induced by either chronic hypoxia (18) or MCT (7), as well as a 4-day-organoid culture of pulmonary artery in vitro (19). The ionic mechanism for developing rhythmic contraction has been explained by membrane depolarization activating L-type calcium channels, which is balanced by calcium-activated potassium channel activity (19) and also by calcium-induced calcium release (7,18).…”
Section: Discussionmentioning
confidence: 99%
“…The ionic mechanism for developing rhythmic contraction has been explained by membrane depolarization activating L-type calcium channels, which is balanced by calcium-activated potassium channel activity (19) and also by calcium-induced calcium release (7,18). In addition, we previously suggested that PGH 2 might be involved in the stretch-induced rhythmic contraction of pulmonary arteries of MCT-PHR, because indomethacin and the PGH 2 /thromboxane A 2 receptor antagonist ), which were expressed in the bathing solution containing 100 μM of RGD-peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Isometric Contraction Measurement. Isometric contractions were measured in rings from IPAs that were mounted in vertical 5-ml organ baths of a computerized isolated organ bath system (IOX, EMKA Technologies, Paris) as described (17). Baths were filled with Krebs-Henseleit solution (composition in mM: 118.4 NaCl͞4.7 KCl͞2.5 CaCl 2 ͞1.2 MgSO 4 ͞1.2 KH 2 PO 4 ͞25 NaHCO 3 ͞ 11.1 D-glucose, pH 7.4) maintained at 37°C and bubbled with a 95% O 2 ͞5% CO 2 gas mixture.…”
Section: Methodsmentioning
confidence: 99%